التوجيه الحجاجي لبلاغو في سور الطواسين من القرآن الكريم - باي خولة; دحمري فاطمة الزهرة (University of El-oued, 2025)
يُعدّ التوجيه الحجاجي في القرآن الكريم ركيزة بيانية تُسهم في إقناع المتلقي، وتحريره من أسر الشك والتردد، إذ جاء الحجاج القرآني مشبعًا بروح البلاغة، مفعمًا بحسن البيان، لا يكتفي بمخاطبة الظاهر من الأفعال، بل ينفذ إلى أعماق النفس وأسرارها، مستحضرًا في الوقت ذاته حال المخاطبين، وسياقاتهم النفسية والاجتماعية، ليرتقي بالخطاب إلى أسمى درجات التأثير والإقناع. وقد جاءت هذه الدراسة لتكشف عن هذا الجانب من خلال بنية ثلاثية قُدّمت بمقدمة تأطيرية، تلتها فصول ثلاثة، الأول منها نظري الطابع الموسوم بـ "البلاغة والحجاج تكامل وتوجيه"، أما الثاني والثالث فخصّصا للتحليل التطبيقي الموسومان على هذا الترتيب "التوجيه الحجاجي للبلاغة القديمة في سور الطواسين" و"التوجيه الحجاجي للبلاغة الجديدة في سور الطواسين". أبرز ما خلص إليه هذا البحث أنّ سور الطواسين تجسّد نموذجًا متكاملًا للحجاج القرآني، حيث تضافرت فيها البلاغة والأسلوب والمقاصد الدعوية في بناء خطاب مؤثر ومقنع، ارتكز على الدعوة إلى التوحيد، والرد على شبهات المشركين، وتثبيت قلب النبي صلى الله عليه وسلم. كما تبيّن أن الخطاب القرآني يتميّز ببنية حجاجية فريدة، جمعت بين جمال التعبير وقوة الحجة، مستعينًا بأساليب متنوعة كالاستعارة، والتمثيل، مما أكسبه طابعًا شاملًا وفاعلًا في النفوس. Argumentative guidance in the Holy Qur’an is a rhetorical cornerstone that contributes to persuading the audience and freeing them from doubt and hesitation. Qur’anic argumentation is rich in eloquence and marked by clarity of expression; it does not merely address outward actions but penetrates the depths of the soul and its secrets. At the same time, it takes into account the state of the audience and their psychological and social contexts, elevating the discourse to the highest levels of impact and persuasion. This study comes to shed light on this dimension through a tripartite structure, beginning with a framing introduction, followed by three chapters. The first is theoretical in nature, titled "Rhetoric and Argumentation: Integration and Guidance." The second and third are devoted to applied analysis, respectively titled "Argumentative Guidance in Classical Rhetoric within the Ṭawasin Chapters" and "Argumentative Guidance in Modern Rhetoric within the Ṭawasin Chapters." The study concludes that the Tawasin chapters exemplify a comprehensive model of Qur’anic argumentation, wherein rhetoric, stylistic elegance, and missionary objectives converge to form a persuasive and impactful discourse. This discourse is fundamentally rooted in the call to monotheism, the refutation of polytheistic objections, and the fortification of the Prophet’s heart peace be upon him. The research also reveals that the Qur’anic discourse is marked by a unique argumentative structure that harmonizes the beauty of expression with the strength of reasoning. It employs a variety of rhetorical devices such as metaphor and analogy, endowing it with a profound and resonant influence on the hearts and minds of its audience.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: الحجاج، البلاغة، التوجيه الحجاجي، سور الطواسين; Argumentation; Rhetoric; Argumentative Guidance; Ṭawasin Chapters.